Short stature as an independent risk factor for cephalopelvic disproportion in a country of relatively small-sized mothers - Toh-adam R. (2014)
Objective: To clarify the relationship between maternal height and cesarean rate due to cephalopelvic disproportion (CPD) in singleton pregnancies among ethnic groups of relatively short stature. Methods: A retrospective cohort study was performed on Thai singleton pregnancies at gestational age of more than 34 weeks. Logistic regression analysis was performed to correlate the maternal height and a risk for CPD. The short stature was defined by a cut-off value at 5th percentile ranking. Odds ratio for CPD was determined. Results: Of 11,026 recruited, 9,198 were available for analysis. Considering cut-off value of 145 cm, short stature was significantly associated with higher rate of CPD with odds ratio of 2.4 (95% CI 1.8-3.0). The odds = exp(4.048 - 0.042 × Ht). After control of other variables, the relationship between maternal height and rate of CPD was still high. Conclusion: Mothers with short stature were significantly correlated with a higher rate of CPD, even after control of birth weight, parity and type of attendance. Clinical points could be drawn from this study including (1) definition of short statue must be developed for particular geographic or ethnic groups. In Thai population, using 145 cm as a cut-off value, odds of CPD is 2.4; (2) Probability of CPD may be estimated by maternal height as a single variable or multiple variables using logistic regression equations. © 2011 The Author(s).